Plasmonic nanohole array for enhancing the SERS signal of a single layer of graphene in water. Issue 1 (December 2017) - Mahigir, Amirreza; Chang, Te-Wei; Behnam, Ashkan; Liu, Gang; Gartia, Manas; Veronis, Georgios
Abstract We numerically design and experimentally test a SERS-active substrate for enhancing the SERS signal of a single layer of graphene (SLG) in water. The SLG is placed on top of an array of silver-covered nanoholes in a polymer and is covered with water. Here we report a large enhancement of up to 2 × 105 in the SERS signal of the SLG on the patterned plasmonic nanostructure for a 532 nm excitation laser wavelength. We provide a detailed study of the light-graphene interactions by investigating the optical absorption in the SLG, the density of optical states at the location of the SLG, and the extraction efficiency of the SERS signal of the SLG. Our numerical calculations of both the excitation field and the emission rate enhancements support the experimental results. We find that the enhancement is due to the increase in the confinement of electromagnetic fields on the location of the SLG that results in enhanced light absorption in the graphene at the excitation wavelength. We also find that water droplets increase the density of optical radiative states at the location of the SLG, leading to enhanced spontaneous emission rate of graphene at its Raman emission wavelengths.